Pengalaman Nyata di Dunia Kerja pada Jurusan Bahasa dan Seni Universitas Palangka Raya - Nabila Salwa; Rojali Rojali; Misnawati Misnawati; Linggua Sanjaya Usop; Yesni Nopi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe how to overcome the limited time for public speaking practice which results in the lack of readiness of Field Work Practice (PKL) participants in discussions and debates, as well as improving ineffective communication between PKL participants and trainers so that the learning process can run more smoothly. A descriptive qualitative approach was used to understand the experiences of participants during PKL at the Language and Arts Department, Palangka Raya University, focusing on exploring the work environment, work ethic, and social relationships. The location of the study was at the Language and Arts Education Department, Palangka Raya University with the research subjects being students who had undergone PKL for three months. Data were collected through observation, in-depth interviews, and documentation. The results of the study showed that limited time for public speaking practice resulted in a lack of readiness of participants in facing discussion and debate situations. The solutions implemented included adding practice sessions outside official hours and on weekends. In addition, the lack of effective communication between PKL participants and trainers was identified as an obstacle in the learning process. To overcome this problem, better communication media, such as social media groups or messaging applications, were implemented to facilitate the exchange of information.